Prevalence of Methicillin-Resistant Staphylococcus aureus in a Canadian Inner-City Shelter - Tom A Szakacs; Baldwin Toye; Jeffrey M Turnbull; Wendy Muckle; Virginia R Roth (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) colonization is increasingly of concern in community settings. However, despite a recent outbreak in Calgary, Alberta, data on the prevalence of MRSA in Canadian communities are lacking. Globally, few studies have been performed in high-risk groups such as inner-city populations.